Ion-Pair Complexes of Pyrylium and Tetraarylborate as New Host-Guest Dyes: Photoinduced Electron Transfer Promoting Radical Polymerization - Santos, Willy G. [UNESP]; Budkina, Darya S.; Santagneli, Silvia H. [UNESP]; Tarnovsky, Alexander N.; Zukerman-Schpector, Julio; Ribeiro, Sidney J. L. [UNESP] (American Chemical Society (ACS), 2019)
Ultrafast transient absorption spectroscopy, NOESY-NMR, and EPR spectroscopy shed light on how π-πstacking interactions combined with electrostatic interactions can be used to form stable ion-pair complexes between pyrylium and tetraarylborate ions in which the interaction of the π-delocalized clouds promotes the observation of new radiative processes and also electron transfer processes excitation using visible light. The results exhibit a striking combination of properties, chemical stability and photophysical and photochemical events, that make these ion-pair complexes as a step toward the realization of chromophore/luminescent materials and also their use as a new monophotoinitiator system in radical polymerization reactions.